Analisis Rasio Aktivitas Untuk Mengukur Tingkat Efektivitas Keuangan PT Kalbe Farma Tbk Periode Tahun 2019 - 2021 - Tasha Alifia Deffianie; Etika Sabariah (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
PT Kalbe Farma Tbk is an industrial company engaged in the pharmaceutical sector that carries out processing, scientific, technical and supporting businesses that produce prescription drug products, nutritional products and medical devices supported by a strong distribution network. At the time of the 2019 Covid pandemic, the pharmaceutical industry gained a considerable increase. The purpose of this study is to determine financial performance through the ratio of activity in the turnover of receivables, working capital, fixed assets, total assets and stocks. The method of data collection techniques in thesis preparation is documentation and uses a non-statistical quantitative approach. The data used in the study came from secondary data, namely the company's financial statements for the period 2019 – 2021. The results obtained from the study show that the analysis of the financial activity ratio of PT Kalbe Farma Tbk from 2019 – 2021 when viewed from the turnover of receivables, working capital, fixed assets, total assets and inventories is declared ineffective because the turnover value fluctuates every year and is still below the industry standard average activity ratio turnover, this is because the company has not maximized its performance in collecting receivables so that embedded working capital The bigger and in inventory has not been able to manage inventory optimally.